The genus Myrsidea Waterston (Phthiraptera: Menoponidae) from tyrant-flycatchers (Passeriformes: Tyrannidae), with descriptions of 13 new species - Price, Roger D.; Hellenthal, Ronald A.; Dalgleish, Robert C. (Zootaxa, 2005)
The two species of previously named Myrsidea from tyrant-flycatchers are redescribed. Thirteen new species are described and illustrated. The new species and their type hosts are: Myrsidea pitangi ex Pitangus sulphuratus (L.), Myrsidea seversoni ex Tyrannus verticalis Say, Myrsidea melancholici ex Tyrannus melancholicus Vieillot, Myrsidea barbati ex Myiobius barbatus (J. F. Gmelin), Myrsidea flaviventris ex Tolmomyias flaviventris (Wied), Myrsidea similis ex Myiozetetes similis (Spix), Myrsidea elaeniae ex Elaenia flavogaster (Thunberg), Myrsidea contopi ex Contopus cinereus (Spix), Myrsidea oleaginei ex Mionectes oleagineus (M. H. K. Lichtenstein), Myrsidea neocinereae ex Serpophaga cinerea (Tschudi), Myrsidea cayanensis ex Myiozetetes cayanensis (L.), Myrsidea olivacei ex Mionectes olivaceus Lawrence, and Myrsidea spadicei ex Attila spadiceus (J. F. Gmelin). Keys are provided for the identification of females and males of the 15 Myrsidea species known from the Tyrannidae.